2017
DOI: 10.1128/jvi.01824-16
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteinase 9 Facilitates Hepatitis B Virus Replication through Binding with Type I Interferon (IFN) Receptor 1 To Repress IFN/JAK/STAT Signaling

Abstract: Hepatitis B virus (HBV) infection may cause acute hepatitis B, chronic hepatitis B (CHB), liver cirrhosis, and hepatocellular carcinoma (HCC). However, the mechanisms by which HBV evades host immunity and maintains chronic infection are largely unknown. Here, we revealed that matrix metalloproteinase 9 (MMP-9) is activated in peripheral blood mononuclear cells (PBMCs) of HBV-infected patients, and HBV stimulates MMP-9 expression in macrophages and PBMCs isolated from healthy individuals. MMP-9 plays important … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 68 publications
0
47
0
Order By: Relevance
“…Moreover, Chen et al. have shown that the matrix metalloproteinase 9 (MMP‐9) is up‐regulated in PBMCs of chronic hepatitis B patients and can be activated by HBV in PBMCs and macrophages in vitro . This up‐regulation may favour the infection as the authors further showed that MMP‐9 enhanced HBV replication in hepatocytes through binding to IFNAR1 (IFNα receptor 1), inducing its ubiquitinylation and degradation (Figure , path#2).…”
Section: Interaction Between Liver Mφ and Hbvmentioning
confidence: 98%
“…Moreover, Chen et al. have shown that the matrix metalloproteinase 9 (MMP‐9) is up‐regulated in PBMCs of chronic hepatitis B patients and can be activated by HBV in PBMCs and macrophages in vitro . This up‐regulation may favour the infection as the authors further showed that MMP‐9 enhanced HBV replication in hepatocytes through binding to IFNAR1 (IFNα receptor 1), inducing its ubiquitinylation and degradation (Figure , path#2).…”
Section: Interaction Between Liver Mφ and Hbvmentioning
confidence: 98%
“…HBV core-associated DNA was purified according to the protocol described in our previous study [18]. In brief, the cells were lysed in lysis buffer (50 mM Tris-HCl [pH 7.0], 0.5% NP-40) on ice and centrifuged for 1 min at 10,000× g. The supernatant was treated with 10 mM MgCl2 and DNaseI for 1 h at 37 • C. Protein was digested with proteinase K and 1% SDS overnight.…”
Section: Hbv Dna Quantificationmentioning
confidence: 99%
“…The top ten enriched pathways were the Jak‐STAT signalling pathway, the p53 signalling pathway, apoptosis and the role of mitochondria in apoptotic signalling (Figure B). All of these pathways are closely associated with HBV infection or cell apoptosis. It appears that upon treatment with H11, the differentially expressed lncRNAs were enriched in apoptotic‐related pathways resulting in suppression of the replication and spread of HBV.…”
Section: Resultsmentioning
confidence: 99%
“…Pathway analysis of lncRNAs identified the Jak‐STAT signalling pathway, the p53 signalling pathway, apoptosis and the cytochrome c‐mediated apoptotic response. It has been demonstrated that repression of Jak‐STAT signalling is beneficial to HBV replication …”
Section: Discussionmentioning
confidence: 99%